Social and biological determinants of iron deficiency anemia Determinação social e biológica da anemia ferropriva - Rosângela Minardi Mitre Cotta; Fabiana de Cássia Carvalho Oliveira; Kelly Alves Magalhães; Andréia Queiroz Ribeiro; Luciana Ferreira da Rocha Sant'Ana; Silvia Eloíza Priore; Sylvia do Carmo Castro Franceschini (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
This cross-sectional study aimed to identify the social and biological determinants of anemia in children enrolled in the Brazilian Income Transfer Program (PBF). The study evaluated 446 children (69.1% of the total enrolled) ranging from 6 to 84 months of age, of whom 262 were receiving the income transfer (60.2% of the beneficiaries) and 184 were not (87.6% of the non-beneficiaries). Testing for anemia was performed with the Hemocue portable hemoglobinometer, and the cutoff points were set at 11.0 and 11.5g/dL, according to age bracket. The data were analyzed using Poisson hierarchical regression with robust variance for multivariate analysis. There was no difference in the anemia prevalence rates between the beneficiary and non-beneficiary groups. Risk factors for anemia were low paternal schooling, cesarean birth, consumption of untreated water, stunting, and age less than 24 months. Prevalence of anemia in the group of non-beneficiary children under two years of age was significantly higher than in the beneficiary group in the same age bracket, suggesting the importance of the PBF income transfer for preventing anemia in children. Neste estudo transversal, objetivou-se conhecer a determinação social e biológica da anemia em crianças cadastradas no Programa Bolsa Família (PBF). Foram avaliadas 446 crianças (69,1% do total cadastrado) com idade entre 6 e 84 meses, sendo que 262 (60,2%) recebiam o benefício, e 184 (87,6%) não recebiam. O teste de anemia foi realizado com o hemoglobinômetro portátil Hemocue, e os pontos de corte adotados foram 11,0 e 11,5g/dL, segundo a faixa etária. Utilizou-se regressão de Poisson hierarquizada com variância robusta para análise multivariada. Não houve diferença entre as prevalências de anemia entre os grupos beneficiários e não-beneficiários. Os fatores de risco para essa carência foram baixa escolaridade paterna, parto cesariano, consumo de água sem tratamento, baixa estatura e idade inferior a 24 meses. A prevalência de anemia no grupo de crianças menores de dois anos não-beneficiárias foi significantemente maior do que no grupo beneficiário de mesma idade, o que sugere a importância do benefício do PBF no combate à anemia em crianças.